PERLINDUNGAN HUKUM TERHADAP PASIEN PESERTA BPJS DALAM PENANGANAN MEDIS DI RUMAH SAKIT PRIMA PEKANBARU - Risfa Anesa; Jambi Luna Maisyarah; Esprida Hotma Dame (Humantech : Jurnal Ilmiah Multidisiplin Indonesia, 2021)
The purpose of the study was to analyze the legal protection of BPJS participantpatients in medical treatment at a private hospital in Pekanbaru City and theobstacles in its protection. This type of research is normative law. The data sourcecomes from secondary data. The results of this study are legal protection for BPJSparticipant patients in medical treatment at private hospitals in Pekanbaru City thatthe government has issued Law Number 40 of 2004 namely the Health Insuranceprogram for BPJS participant patients where every hospital is to provide services toparticipants in utilizing their right to seek treatment at designated health facilitiesfor free, but there are obstacles in legal protection for patients participating in BPJSbecause there are still health service facilities and infrastructure that are not up tostandard and there is still unfulfilled/availability of medicines and medicalconsumables needed.